Pengaruh Variasi Putaran Benda Kerja Dan Feeding Menggunakan Metode Pemakanan Tangensial Posisi Up Pada Proses Turn-Milling Terhadap Kekasaran Permukaan - Hendro Sulistiono; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Surface roughness is a very important factor in the production of the one turn-milling process. Turn-milling is a combined machining process of turning and milling processes with additional tools (cutting) that rotate simultaneously with the rotation of the workpiece. Turn-milling processes are classified in orthogonal turn-milling methods, co-axial turn-milling, tangential turn-milling and each feeding method has an up and down feeding position. The resulting surface quality is also affected by the parameters of the machining process in the form of workpiece rotation and feeding. The purpose of this research is to determine the effect of parameters on surface roughness and to know the optimal parameters of surface roughness by doing tangential process turn-milling position up. By varying the parameter variables, the surface roughness produced in this study is influenced by the rotation of the workpiece and feeding. The slower rotation of the workpiece then the lower the resulting surface roughness value, while the smaller feeding then the smaller the resulting surface roughness value from the tangential turn-milling process with a constant tool rotation at 25,000 rpm. The optimal parameter is the rotation of 400 rpm workpiece with 0.051 mm/rev roughness value of 1.632 μm found on the N7 roughness.Keyword: Turn-milling, Tangential turn-milling, Rotation, Feeding, Surface roughness.